Menakar Preferensi Musik di Kalangan Remaja: Antara Musik Populer dan Musik Klasik - de Fretes, Daniel; Bonggaminanga, Putri Isydora (Universitas Hamzanwadi, 2021)
This article aims to explain the choice of music among adolescents with a focus on popular music and classical music. The research was conducted on 12 Junior High School (SMP) students at 12-14 years. The study was conducted qualitatively through virtual interviews using Zoom Cloud Meeting. The Sampling technique used purposive sampling based on the specified criteria: (1) active as music listeners; (2) listening to music for 120 minutes per week; (3) willing to take part in the interview stage in 180 minutes. Observations were made on the adolescents' responses to visual, audio, and audiovisual shows presented by researchers through Microsoft Powerpoint during the interview session. This study shows that teenagers tend to choose popular music and classical music due to several factors, namely the experience of listening to music and the environment in which they live. Adolescents who choose classical music are supported by their environment and family background who are familiar with classical music. Classical music is less popular among teenagers because of limited references and difficulties in enjoying or interpreting music without lyrics. Teenagers choose popular music for its uplifting beats and understandable lyrics.Â This research presents the heterogeneity of subjects from different cities which can open up opportunities for further studies.